1970
DOI: 10.1071/bi9701109
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of C18 Unsaturated Fatty Acids by Pure Cultures of a Rumen Micrococcus

Abstract: Approximately 70% of the fatty acids present in plant lipids are unsaturated; the major component is cis-9,cis-12,cis-15-octadecatrienoic acid (Garton 1963). After ingestion by ruminants, these acids are readily hydrogenated by microorganisms in the rumen to form a complex mixture of positional and geometrical C18 isomers (Shorland et al. 1957;Ward, Scott, and Dawson 1964;Wilde and Dawson 1966;Kemp and Dawson 1968). Kemp and Dawson (1968) showed that the first stage in the hydrogenation of linolenic acid by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1971
1971
2003
2003

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…For this reason, it has been difficult to characterize the reactions involved in the hydrogenation process. Several rumen bacteria have been identified as possessing the ability to hydrogenate 18-carbon, unsaturated fatty acids (19,21,23,28); however, only Butyrivibrio fibrisolvens strain A38 has been studied in detail (13,14,16). A particulate isomerase from this bacterium initially isomerizes linoleic acid to cis-9, trans-11-octadecadienoic acid.…”
mentioning
confidence: 99%
“…For this reason, it has been difficult to characterize the reactions involved in the hydrogenation process. Several rumen bacteria have been identified as possessing the ability to hydrogenate 18-carbon, unsaturated fatty acids (19,21,23,28); however, only Butyrivibrio fibrisolvens strain A38 has been studied in detail (13,14,16). A particulate isomerase from this bacterium initially isomerizes linoleic acid to cis-9, trans-11-octadecadienoic acid.…”
mentioning
confidence: 99%
“…The chemical structure of CLA1 was not identiˆed: it may be cis-9,trans-11-or trans-9,cis-11-18:2. 5-7) Some studies found that linoleic acid is converted to 9,11-18:2 by several species of rumen bacteria [8][9][10][11][12][13][14][15] and by dairy starter cultures. 16) However, to our knowledge, exact identiˆcation of the geometric conˆguration of the 9,11-18:2 produced has not been done.…”
mentioning
confidence: 99%
“…The ability of microwave energy to cause Isomerlzation of fatty acids in other foods needs to be studied. Rumen micrococci have been shown to cause isomerlzation of fatty acids (Mills et al, 1970). A species of Micrococcus is used as a starter culture in the preparation of summer sausages.…”
mentioning
confidence: 99%